UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MATERI HAK DAN KEWAJIBAN DENGAN MENGGUNAKAN MODEL KOOPERATIF LEARNING MELALUI LKPD DI KELAS 3 SDN 19 SISTIUNG - Dila santika Fuji febriani, ikke rosdiana, lisda dewi anggraini (Jurnal Dharma PGSD, 2025)
Abstract: This study was conducted with the aim of improving the learning outcomes of third-grade students at SDN 19 Sitiung on the topic of rights and obligations through the implementation of a cooperative learning model supported by the use of student worksheets (LKPD). The type of research applied was Classroom Action Research (CAR), carried out in two cycles. Each cycle consisted of the stages of planning, implementation, observation, and reflection (Mutia et al., 2022). Data were collected through teacher and student activity observations, learning outcome tests, and documentation. The results showed a significant improvement in students’ learning outcomes. Notably, the second cycle demonstrated substantial progress, indicating the success of implementing the cooperative learning model assisted by LKPD. Based on these findings, it can be concluded that this instructional strategy effectively encourages active student participation and enhances their understanding of the material on rights and obligations.